Microbial multiplication in raw milk stored in direct expansion bulk tanks Multiplicação microbiana no leite cru armazenado em tanques de expansão direta - Reche N.L.M.* (2015)
© 2015, Universidade Federal de Santa Maria. All Rights Reserved.The purpose of this study was to evaluate the effect of the cold storage period of raw milk in bulk tanks, using two and four milking models, on total bacterial count (TBC) and psychrotrophic bacterial count (PBC). A total of 19 dairy farms, located in West and Uplands of the Santa Catarina State - Brazil, was been evaluated. Each dairy farm had direct expansion bulk milk tank and an occupancy rate varying from 60% to 100%. Samples were collected before and after each milking procedure to determine PBC and TBC, totalizing four milking and a storage period of 36 hours. The storage time did not affect TBC and PBC (P>0.05). The bulk tank model only affected the PBC (P < 0.05), with two–milking model presenting a lower mean than four-milking model (3.61±0.104 and 4.00±0.120CFU mL-1 (log10)). It was possible to conclude that bulk tanks, when used properly concerning raw milk volume to be chilled, allow the TBC and PBC to remain stable in the transportation systems of raw milk to the industry each 48 hours.